Validação e categorização da escala de crenças dos pais de recém-nascidos prematuros hospitalizados - Piva, Eloeth Kaliska (2017)
The hospitalization of the newborn in a Neonatal Intensive Care Unit (NICU) is a source of stress for the parents, affecting the parental role and the capacity of care. Thus, the present study aimed to perform the translation, cultural adaptation, psychometric validation, categorization of scores and clinical validation of the Neonatal Intensive Care Unit: Parental Belief Scale (NICU: PBS) for Brazilian portuguese, with parents of children premature hospitalized. This is a methodological study, with quantitative analysis involving fathers and/or mothers of premature newborns admitted to the NICU or the Intermediate Care Unit (ICU) in a university in western Paraná. The cultural adaptation of the instrument attended to the sequence: (1) translation of the instrument from the source language into the target language, (2) back translation, (3) analysis of the version synthesized by a committee of judges, (4) pre-test (n=08), (5) re-examination of scores. Finally, reliability assessment with the test-retest (n=23), and validity with clinical validation (n=76). In the evaluation of the committee of judges there was agreement for the translation of 90% and Kappa of 0.71 indicating substantial agreement. The pre-test revealed an understanding of 87.5% of parents regarding the application of the instrument. The test-retest obtained an Intraclass Correlation Coefficient (ICC) of 0.98 and Cronbach's Alpha of 0.92, revealing excellent stability and high internal consistency. The validity of the construct was based on the confirmatory and exploratory factorial analysis of data from 99 fathers and/or mothers. The Kaiser Meyer-Olkin (KMO) test of 0.86 indicated good fit of the sample. The E model, evidenced by the exploratory factorial analysis, obtained better adjustments and supported a factorial structure in three factors: trust in parental role, parent and child interaction, and parental knowledge in the NICU. With the categorization of the scores obtained in the application of the instrument, the individuals were classified into: a) "capacity of care" (scores between 90 and 72), with 35 fathers and/or mothers; B) "moderate capacity of care" (scores between 71 to 54), with 50 fathers and/or mothers; and c) "moderate insufficiency of the capacity of care" (scores ranging from 53 to 36), with 14 fathers and/or mothers. The category "Insufficiency of the capacity of care" (scores between 35 and 18), did not obtain individuals who in this range. In the comparison between sociodemographic and clinical data, a significant statistical association was found between the parents' classification groups with the age of the children in addition to the preterm infant. And the Principal Components Analysis showed an inverse relationship between the scale scores with family income, age and maternal schooling, with a statistically significant association for the family income. The scale proved adequate and reliable for the application with fathers and/or mothers of hospitalized preterm infants, presenting themselves as a tool to guide the work of the health team.